2002
DOI: 10.1097/00000658-200205000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Results of 281 Consecutive Total Laparoscopic Roux-en-Y Gastric Bypasses to Treat Morbid Obesity

Abstract: ObjectiveTo determine the safety and efficacy of laparoscopic Rouxen-Y gastric bypass for the treatment of morbid obesity. Summary Background DataLaparoscopic Roux-en-Y gastric bypass is a new and technically challenging surgical procedure that requires careful study. MethodsThe authors attempted total laparoscopic Roux-en-Y gastric bypass in 281 consecutive patients. Procedures included 175 proximal bypasses, 12 long-limb bypasses, and 9 revisional procedures from previous bariatric operations. The gastrojeju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
261
5
34

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 526 publications
(314 citation statements)
references
References 11 publications
14
261
5
34
Order By: Relevance
“…The other two mentor faculty, both with extensive experience with open gastric bypass over many years, began to perform LRYGB closer to initiation of the fellowship, with the assistance of their experienced colleague. While it is possible that the MI faculty had not completely climbed their own learning curves for LRYGB during the early period of fellowship training and that this could represent a bias in the current study, the MI demonstrated CRO for LRYGB comparable to other published benchmark data for cases performed during the period of training [25]. Specifically, the rates of significant complications for the MI, detailed in Table 2, were within the ranges established in landmark publications describing experience with LRYGB [26][27][28].…”
Section: Discussionmentioning
confidence: 48%
“…The other two mentor faculty, both with extensive experience with open gastric bypass over many years, began to perform LRYGB closer to initiation of the fellowship, with the assistance of their experienced colleague. While it is possible that the MI faculty had not completely climbed their own learning curves for LRYGB during the early period of fellowship training and that this could represent a bias in the current study, the MI demonstrated CRO for LRYGB comparable to other published benchmark data for cases performed during the period of training [25]. Specifically, the rates of significant complications for the MI, detailed in Table 2, were within the ranges established in landmark publications describing experience with LRYGB [26][27][28].…”
Section: Discussionmentioning
confidence: 48%
“…This report fails to mention the shorter length of hospital stay, the significant decrease in pain, and wound complications the early improvement in quality of life and earlier return to work with the laparoscopic approach. [79][80][81][82][83] When evaluating the adjustable laparoscopic gastric band, the authors of the TEC report fail to mention the significantly lower postoperative mortality of 0.05% 97-100 as compared to either the open or laparoscopic gastric bypass (0.5-2%).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, placement of an adjustable laparoscopic gastric band may be safer for frail, high-risk patients. When analyzing the risks and benefits of laparoscopic gastric bypass, the early benefits of the laparoscopic vs the open approach [79][80][81][82][83] were ignored in the TEC study, through not including decreased postoperative pain, decreased wound complications and earlier improvements in quality of life and return to work. The significant benefits of the laparoscopic approach are driving patients to choose laparoscopicoperations.…”
Section: Rcts and Levels Of Evidencementioning
confidence: 99%
“…Stenosis of gastrojejunal anastomosis was found in only one patient (2.4%), a little below the percentages reported by the literature (3-27%) (14-18) . DeMaria et al have evaluated 281 patients and reported this event in 6.6% of cases (17) . Ulcers may be caused by exposure to gastric acids from the gastrojejunal anastomosis or by ischemia.…”
Section: Discussionmentioning
confidence: 99%